Behavioral Finance in Brazil: applying the prospect theory to potential investors - Emiko Yoshinaga, Claudia; Borges Ramalho, Thiago (Review of Business Management, 2014)
The premise of unbounded rationality defended by the Efficient Market Hypothesis is challenged by the theoretical framework that involves Behavioral Finance, whose basis, Kahneman and Tversky’s Prospect Theory (1979), questions the Expected Utility Theory, an important element of Neoclassical Economics, as basis for decisionmaking. This research aims to replicate the empirical research of Kahneman and Tversky’s seminal article (1979) to evaluate the decisionmaking process of employees (potential investors) from a major national financial institution. The results of this study were compared to those obtained in the original article and to other similar studies. The questionnaire employed was an adaptation of the one originally used, so that we could test, in the studied sample, the applicability of the Prospect Theory, more specifically with regard to Certainty, Reflection and Isolation Effects. We also analyzed differences in the decision-making process considering respondents’ attributes (gender, age and income). The results confirmed that behavioral effects do exist, and proved that a large portion of the sample presented significant inconsistency in their choices according to Expected Utility Theory principles, highlighting that their decisions were not made according to strictly rational behavior. Furthermore, we analyzed the relationship between violations and investor characteristics by estimating a linear model. Results indicate that both age and level of income were negatively related to total violations.